Nicotine dependence and symptom severity in patients with schizophrenia in Morocco (Bangladesh Journal of Medical Science, 2024)
Background The prevalence of smoking among patients suffering from schizophrenia is significantly higher than in the general population. Studies of the correlation between tobacco consumption and psychotic symptoms, as assessed by the PANSS test, have yielded different results. It is therefore interesting to examine how nicotine dependence levels impact symptom severity. Objectives: The aim of our study is to describe the degree of dependence in schizophrenic patients and to determine the correlation with the severity of clinical symptoms.Method and Materials 172 patients hospitalized at the Ar-razi hospital in Salé. Sociodemographic data were collected using a questionnaire. Symptom severity was assessed using the Positive and Negative Syndromic Schizophrenia Scale (PANSS). And the degree of tobacco dependence was assessed using the Fagerström Test (FTND).Result Our main results show that the average age of our patients is 31.76 years. 80.2% use atypical antipsychotics, 79.1% use tobacco and 77.9% use cannabis. 43.6% showed a mild dependence on nicotine, while 25.6% had a high dependence, and 30.8% a very high dependence. The correlation test showed a significant association between the degree of nicotine dependence and PANSS score (P